1994
DOI: 10.1143/jjap.33.18
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscope Observation of Cubic GaN Grown by Metalorganic Vapor Phase Epitaxy with Dimethylhydrazine on (001) GaAs

Abstract: Cross-sectional transmission electron microscope observation has been performed on the microstructure of GaN films grown on a (001) GaAs substrate by metalorgahic vapor phase epitaxy (MOVPE) using 1,1-dimethylhydrazine (DMHy) and trimethylgallium (TMG) as the sources of nitrogen and gallium, respectively. Before the deposition, the surface of the substrate was nitrided with DMHy. High-resolution images and electron diffraction patterns confirmed that the GaN films have a zincblende structure (β-GaN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…1 and 2, it is concluded that the formation of a smooth and uniform nucleation layer (AlGaN) and suppression of {111} facets formation were essential to realize high phase purity c-GaN epilayer growth. Similar results were reported by Kuwano et al [4] with c-GaN/GaAs (001). Figure 6 shows a 2θ-ω XRD scan using along the [100] axis of a c-GaN epilayer grown on an AlGaN surface formed by 10 seconds nitridation.…”
Section: Fig 2 Afm Images Of After Nitridation Onsupporting
confidence: 91%
See 1 more Smart Citation
“…1 and 2, it is concluded that the formation of a smooth and uniform nucleation layer (AlGaN) and suppression of {111} facets formation were essential to realize high phase purity c-GaN epilayer growth. Similar results were reported by Kuwano et al [4] with c-GaN/GaAs (001). Figure 6 shows a 2θ-ω XRD scan using along the [100] axis of a c-GaN epilayer grown on an AlGaN surface formed by 10 seconds nitridation.…”
Section: Fig 2 Afm Images Of After Nitridation Onsupporting
confidence: 91%
“…Recently, improvements in the crystallinity of nitride crystal growth for short nitridation times have been studied [2,3]. The nitridation process of the initial growth of c-GaN films on GaAs substrate has also been studied [4][5][6].In this work, a dramatic improvement in the reproducibility and stability of c-GaN epilayer growth was achieved by controlling {111} facet formation during the initial stage of growth by optimizing nitridation conditions. The crystallographic properties of the as-grown layers were characterized by reflection high-energy electron diffraction (RHEED) and high resolution X-ray diffraction (HR-XRD).…”
mentioning
confidence: 99%
“…AlN seems to be different. The formation of (Me 2 AlNH 2 ) 3 amides in the gas phase as well as the surface-bound adducts [Me 2 AlNH 3 ] ads was observed [60][61][62]. Nothing is known about InN growth.…”
Section: The Role Of Chemistry In Omvpe Of the Nitridesmentioning
confidence: 99%
“…One drawback, however, is the high toxicity of hydrazine (TLV skin = 0.01 ppm) and the tendency toward explosive decomposition, which is catalyzed by traces of oxidants and various metals. Less dangerous alkyl derivatives of hydrazine, such as (CH 3 ) 2 N -NH 2 , have also been studied, but again gave unwanted carbon impurities at 550-650 • C and a V/III ratio of 160 : 1 [69][70][71]. Using hydrogen azide HN 3 , which is an even more dangerous compound [72], very good nitride films were grown at low temperatures using either OMVPE or MBE techniques [73].…”
Section: The Role Of Chemistry In Omvpe Of the Nitridesmentioning
confidence: 99%
“…For example, an optical cavity is easily formed by cleavage and electrodes can be formed in the vertical configuration. However, the growth of high quality c-GaN epilayers has been prevented from inclusion of stable h-GaN and stacking faults in c-GaN epilayer [6].…”
mentioning
confidence: 99%